R/S financial market analysis - Danilenko , Svetlana (Lietuvos matematikos rinkinys, 2008)
This work discusses the application of R/S analysis to financial markets. The most of the work is devoted to the calculation of Hurst parameter. The Hurst parameters of the Baltic state shares indices are presented.